2019
DOI: 10.1093/restud/rdz044
|View full text |Cite
|
Sign up to set email alerts
|

Mergers, Innovation, and Entry-Exit Dynamics: Consolidation of the Hard Disk Drive Industry, 1996–2016

Abstract: How far should an industry be allowed to consolidate when competition and innovation are endogenous? We develop a stochastically alternating-move game of dynamic oligopoly and estimate it using data from the hard disk drive industry, in which a dozen global players consolidated into only three in the last 20 years. We find plateau-shaped equilibrium relationships between competition and innovation, with heterogeneity across time and productivity. Our counterfactual simulations suggest the current rule-of-thumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In other extensions, one could incorporate cost synergies, or the loss of cost synergies from the mix and match process. As shown in Igami and Uetake () for the hard disk drive industry, the effects of synergies can be significant.…”
Section: Resultsmentioning
confidence: 98%
“…In other extensions, one could incorporate cost synergies, or the loss of cost synergies from the mix and match process. As shown in Igami and Uetake () for the hard disk drive industry, the effects of synergies can be significant.…”
Section: Resultsmentioning
confidence: 98%
“…While most of the discussion so far concentrated on the recent theoretical economic literature, considerable advances have also been made on the empirical front—despite computational challenges and data limitations in finding good proxies for innovation efforts. In particular, Igami and Uetake ( 2020 ) evaluate a structural dynamic oligopoly model that is applied to the hard disk drive industry. They find that mergers can be particularly harmful for innovation when an industry is already concentrated.…”
Section: Innovation Competitionmentioning
confidence: 99%
“…On the other hand, other studies find increases in R&D activity after mergers, including Bertrand (2009), and Entezarkheir and Moshiri (2018) reports increased patenting activity following mergers. 3 Finally, in a recent paper most closely related to ours, Igami and Uetake (2017), focus on the HDD market, estimating a dynamic oligopoly model, in which merger decisions are endogenous. By employing hypothetical merger policies as counterfactuals, they show that the optimal policy should block mergers if there are 6 or fewer players in the HDD market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their 2011/12 investigation the European Commission concluded that the two are not in the same product market. Igami and Uetake (2017) also acknowledges the difference between HDD and SSD (which may be one of the reasons why SSD firms are excluded from their model of competition). Their justification is based on the argument that there are at least some applications where HDD does not compete with SSD.…”
Section: Independence Of the Control Groupmentioning
confidence: 99%